THE EFFECT OF DUOLINGO IN TEACHING SPEAKING AT THE EIGHTH GRADER - Budiyanto, Darmawan; Ridho, M.Rasyid (English Community Journal, 2024)
This investigation looks at the usefulness of Duolingo in improving speaking abilities among eighth-grade students at SMPN 46 Palembang. The research employs Quantitative method through a quasi-experimental designed with a control and an experimental group. Population was 120 students and the sample selected by random sampling in terms of 60 students as sample in this research. Data collected by speaking test and analysing data by using dependent and independent sample t-test. Results, dependent sample t-test indicate a significant improvement in speaking proficiency after using Duolingo. Independent sample t-test show that Duolingo group outperformed of control group. This study's novelty lies in its contextual application within an Indonesian secondary school, providing localized insights into Duolingo's effectiveness. Conclusion, Duolingo significantly enhances speaking skills among eighth-grade students, offering advantages such as increased engagement, immediate feedback, and personalized learning.